Nutritional And Anti-Nutritional Composition Of Fermented/Pickled Garden Egg (Solanum Aethiopicum L.) - Olasunmbo A Ajayi; Oluwatosin T Awe (Food ScienTech Journal, 2022)
Garden egg (Solanum aethiopicum L.) is highly perishable. Shelf life of the crop can be extended via pickling. Therefore, this study focused to observe the pickled garden egg, in order to make it available in and out of season. Three samples were prepared, namely unpickled (control) garden egg (UPRGE); pickled garden egg in brine with sugar (PGESU); and pickled garden egg with salt (PGESA). Samples were pickled for seven days and evaluated for the nutritional, phytochemicals and sensory qualities using standard methods. On dry weight basis, moisture contents ranged from (1.11 to 1.12 %), protein ranged from (13.8 to 19.5 %), ash ranged from (12.7 to 18.0 %), fiber ranged from (8.5 to 15.8 %), fat ranged from (2.7 to 5.4 %) and the available carbohydrates ranged from (45.1 to 54.3 %). There was significance difference (p<0.05) in protein, ash, crude fiber, and carbohydrates. The mineral compositions were as follows: Potassium (183.0 to 183.7 mg/g), magnesium ranged from (162.3 to 194.5 mg/g), calcium ranged from (105.6 to 207.3 mg/g), copper ranged from (67.9 to 747.1 mg/g) and sodium ranged from (315.4 to 346.2 mg/g). Vitamin C ranged from (3.25 to 3.37 mg/g), saponin ranged from (10.74 to11.58 mg/g) and tannin (1.93 to 2.73 mg/g). Unpickled garden egg was scored higher in all of the sensory attributes. Conclusively, although pickling improves the nutritional composition of garden egg, and reduces the anti-nutritional content, the raw samples were preferred.